2021
DOI: 10.3389/fnins.2021.739236
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reproductive Hormones in Sex Differences in Sleep Homeostasis and Arousal Response in Mice

Abstract: There are various sex differences in sleep/wake behaviors in mice. However, it is unclear whether there are sex differences in sleep homeostasis and arousal responses and whether gonadal hormones are involved in these sex differences. Here, we examined sleep/wake behaviors under baseline condition, after sleep deprivation by gentle handling, and arousal responses to repeated cage changes in male and female C57BL/6 mice that are hormonally intact, gonadectomized, or gonadectomized with hormone supplementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…1). Similar to other reports in rodents [38], we saw that male and female C57BL/6J mice sleep differently at baseline, with the males sleeping on average 58.3% of the light cycle and 22.9% of the dark cycle while females slept 52.0% of the light cycle and 22.6% of the dark cycle (Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1). Similar to other reports in rodents [38], we saw that male and female C57BL/6J mice sleep differently at baseline, with the males sleeping on average 58.3% of the light cycle and 22.9% of the dark cycle while females slept 52.0% of the light cycle and 22.6% of the dark cycle (Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found differences in baseline sleep between male and female mice [38], we confirmed similar sex differences here using our sleep measurements with the PiezoSleep system. We found a main effect of sex on % time asleep in the light cycle (Figure 2A, F(1,102) =30.62, p<0.0001), and a significant interaction of sex vs. time (Fig.…”
Section: Significant Sex Differences In Sleep Baselinessupporting
confidence: 91%
“…There are several limitations to this study. Although male mice were used in this study to reduce the number of mice, female Ptf1a cKO mice may yield different results, as we have showed that the sleep/wake behavior of female mice differs from that of male mice (Choi et al, 2021 ). Compensation for the loss of the cerebellum from the embryonic stage may have weakened the sleep phenotype of Ptf1a cKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…If they showed the same sleep abnormalities as their father F1 mouse, these mice were further used for quantitative trait locus analysis and whole-exome sequencing. Because of the large difference in sleep between males and females, only male mice were used for sleep analysis [30]. This approach identified the genetic mutations responsible for heritable sleep abnormalities, such as the Sik3 gene mutation in the Sleepy mutant pedigree and the Nalcn gene mutation in the Dreamless mutant pedigree [31] (Fig.…”
Section: Dominant Screening Of Sleep-regulating Genesmentioning
confidence: 99%